Big Data from the Perspective of a Sample of Students from Universities in Northern Peru - Matas Terrón, Antonio (2020)
Big Data is a reality that is gradually being incorporated and strongly in all fields of society, including in Education, although late. The objective of this study is to descriptively analyze the general perspective that a sample of 104 university students of Education of Peru has on the Big Data applied to Education. The participating sample was non-probabilistic incidentally. A survey study was conducted, using the VABIDAE scale to collect the data. A psychometric study of the scale was done with the collected data, as well as a descriptive statistical analysis. The results show a positive perception of the participants before Big Data as well as an obvious predisposition to use Big Data services in their professional practice as a source of information. It also highlights the absence of a gender gap. Finally, its possible impact on teacher training is discussed.